Low-Cost Air Gap Metasurface Structure for High Absorption Efficiency Energy Harvesting - Wei Hu; Zhao Yang; Fading Zhao; Guangjun Wen; Jian Li; Yongjun Huang; Daniele Inserra; Zhizhang (David) Chen (International Journal of Antennas and Propagation)
This manuscript deals with the design of a metamaterial-based surface structure for high efficiency wireless power harvesting or collection. Differently from the previously presented structures which require the use of thicker and low-loss (and for this reason high cost) dielectric substrates, the presented work employs a dual-layer structure with a thin low-loss material and an air gap; they allow for the design of very high absorption efficiency metamaterial-based surfaces, with noticeably reduced costs. Furthermore, the air gap thickness can be used as a new degree-of-freedom (more easily adjustable than the thickness of a single-layer structure) for the optimization of other design requirements such as bandwidth or structure sizes. In comparison with other existing designs, the proposed metasurface shows a comparable absorption efficiency of 84.4% but with a larger power collection surface and lower costs.